2017
DOI: 10.1002/bit.26387
|View full text |Cite
|
Sign up to set email alerts
|

A review on comparative mechanistic studies of antimicrobial peptides against archaea

Abstract: Archaea was until recently considered as a third domain of life in addition to bacteria and eukarya but recent studies support the existence of only two superphyla (bacteria and archaea). The fundamental differences between archaeal, bacterial, and eukaryal cells are probably the main reasons for the comparatively lower susceptibility of archaeal strains to current antimicrobial agents. The possible emerging pathogenicity of archaea and the role of archaeal methanogens in methane emissions, a potent greenhouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 188 publications
(280 reference statements)
0
14
0
Order By: Relevance
“…Cultivated members of both of these methanogen clades are hydrogenotrophic and use H 2 and CO 2 for CH 4 formation. Their cell walls contain pseudomurein and have similarities to those found in Gram positive bacteria which may be relevant to their sensitivity to antimicrobial agents (Varnava et al, 2017). Other significant members of the methanogen community in the rumen are methylotrophs, producing CH 4 from methyl-containing substrates, particularly methylamines and methanol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cultivated members of both of these methanogen clades are hydrogenotrophic and use H 2 and CO 2 for CH 4 formation. Their cell walls contain pseudomurein and have similarities to those found in Gram positive bacteria which may be relevant to their sensitivity to antimicrobial agents (Varnava et al, 2017). Other significant members of the methanogen community in the rumen are methylotrophs, producing CH 4 from methyl-containing substrates, particularly methylamines and methanol.…”
Section: Resultsmentioning
confidence: 99%
“…The idea that LAB can be used to reduce CH 4 production in ruminant livestock is not new. Reviews of CH 4 mitigation strategies consistently refer to this possibility (Hristov et al, 2013; Takahashi, 2013; Jeyanathan et al, 2014; Knapp et al, 2014; Varnava et al, 2017). However, research on the topic has been limited and convincing data from animal trials to support this concept are lacking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In archaea, this is achieved mainly through alterations of monounsaturated diethers, isoprenoid hydroxylation, and the tetraether:diether ratio. In bacteria, distinct targets of lipid-based adaptation include mainly variable contents of monounsaturated, short chain, and branched chain fatty acids (Suutari and Laakso 1994;Siliakus et al 2017;Varnava et al 2017). These saturated and monounsaturated lipids, common for many species of archaea in different habitats, including microbiomes in animals and humans, are not readily oxidized at moderate temperatures ("normal" for higher organisms), whereas lipids in thermophilic archaea organisms may get oxidized at "normal" (for them) temperatures up to 122°C (Takai et al 2000;Quince et al 2017).…”
Section: Bacteria Archaea and Fungimentioning
confidence: 99%
“…Original descriptions referred to these compounds as "antimicrobial peptides" or "AMP's" based on the theory that their principal purpose was the direct eradication of bacterial species. However, recent studies have revealed that host defense peptides are capable of eliminating bacteria, viruses, parasites, and even archaea 4,5 and these peptides have displayed critical functions in immunomodulation and wound healing that may actually be more important than their direct actions against infectious agents. 6,7 Structurally and mechanistically, host defense peptides are a diverse class of molecules that can be synthesized through a multi-enzymatic process or ribosomal translation, with or without post-translational modification.…”
Section: Introductionmentioning
confidence: 99%